2008
DOI: 10.1007/s12022-008-9037-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p21cip1, p27kip1, and p16INk4a Cyclin-Dependent Kinase Inhibitors in Papillary Thyroid Carcinoma: Correlation with Clinicopathological Factors

Abstract: In a variety of human malignancies, aberrant expression of proteins involved in the control of cell-cycle progression has been reported. In this study, p21cip1, p27kip1, and p16INk4a cyclin-dependent kinase inhibitors were analyzed to evaluate their usefulness in clinical management of papillary thyroid carcinoma (PTC). Archived material derived from 46 cases of PTC was analyzed immunohistochemically. Protein expression was ascertained on tissue microarrays, and results were correlated with clinicopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Up-regulation of FHIT, p16 and PPAR-γ have also been shown to result in cell-cycle arrest and apoptosis. 13 -15 Previous studies have demonstrated low to absent p16 or FHIT immunoreactivity in thyroid carcinomas 4,16 and, in the present study, their expression in thyroid carcinomas was found to be low. Conversely their expression has been found to be uniformly high in other benign endocrine tumours.…”
Section: H-s Liang Y-h Zhong Z-j Luo Et Al Protein Expression In Differentiated Thyroid Tumours Benign From Malignant Pathology On the Basupporting
confidence: 46%
“…Up-regulation of FHIT, p16 and PPAR-γ have also been shown to result in cell-cycle arrest and apoptosis. 13 -15 Previous studies have demonstrated low to absent p16 or FHIT immunoreactivity in thyroid carcinomas 4,16 and, in the present study, their expression in thyroid carcinomas was found to be low. Conversely their expression has been found to be uniformly high in other benign endocrine tumours.…”
Section: H-s Liang Y-h Zhong Z-j Luo Et Al Protein Expression In Differentiated Thyroid Tumours Benign From Malignant Pathology On the Basupporting
confidence: 46%
“…Although it is possible that p14/p16 up-regulation represents a thyrocyte's attempt to counter the hyperproliferative signals generated by Kras and PI3K, additional studies are warranted to fully understand this finding. Nonetheless, it is worthy of note that CDKN2A up-regulation has been frequently reported in thyroid carcinomas (26-28). …”
Section: Discussionmentioning
confidence: 96%
“…According to recent research, several diagnostic and prognostic markers have been proposed in improving the diagnostic accuracy of papillary thyroid cancer such as Cytokeratin-19 (CK-19), HBME-1, Galectin-3, CD44, CD56, E-cadherin, c-erbB-2, p21 cip1 , p27 kip1 , and p16 ink4a [413]. …”
Section: Introductionmentioning
confidence: 99%